CIRCUIT DESIGN HOUSE DOOR CONTROLLER INTERFACE USING PROGRAMMABLEPERIPHERAL (PPI)-BASED 8255 PERSONAL COMPUTER (PC) - Edy Purwanto; Indrianto. Skom. MT Indrianto. Skom. MT (Jurnal Sistem Komputer, 2008)
The design of the door controller series is a tool that serves to open and close the doorby automatically, without having moved by human power with the desired degrees (inmultiples of 7.2). This tool is very useful especially in the Jakarta metropolitan arealike this because it can minimize the occurrence of theft in the home or the usualdifficulties encountered daily in the open or close the door of the house.This tool uses a stepper motor controlled by the controlling circuit (stepper motordriver). With PPI 8255 as a controller that can be programmed, these devices can beconnected to personal computers or PC so that its operation becomes very easy justby pressing one button on the menu of available options